Regulation of Selective B Cell Autophagy by the Pro-oxidant Adaptor p66SHC - Onnis, Anna; Cassioli, Chiara; Finetti, Francesca; Baldari, Cosima T. (Frontiers in Cell and Developmental Biology, 2020)
p66SHC is a pro-oxidant member of the SHC family of protein adaptors that acts as a negative regulator of cell survival. In lymphocytes p66SHC exploits both its adaptor and its reactive oxygen species-elevating function to antagonize mitogenic and survival signaling and promote apoptosis. As a result, p66SHC deficiency leads to the abnormal expansion of peripheral T and B cells and lupus-like autoimmunity. Additionally, a defect in p66SHC expression is a hallmark of B cell chronic lymphocytic leukemia, where it contributes to the accumulation of long-lived neoplastic cells. We have recently provided evidence that p66SHC exerts a further layer of control on B cell homeostasis by acting as a new mitochondrial LC3-II receptor to promote the autophagic demise of dysfunctional mitochondria. Here we discuss this finding in the context of the autophagic control of B cell homeostasis, development and differentiation in health and disease.